2008
DOI: 10.4321/s0212-71992008000600003
|View full text |Cite
|
Sign up to set email alerts
|

Vigilancia epidemiológica de la intoxicación aguda en el área sur de la Comunidad de Madrid: estudio VEIA 2004

Abstract: INTRODUCCIÓNEl Estudio VEIA examina la IA desde 1979 mediante cortes cuatrienales que recogen todos los casos asistidos en Urgencias del Hospital Universitario 12 de Octubre durante un año (1-7). En el presente artículo exponemos los resultados de 2004. Justifican este importante esfuerzo las grandes variaciones que el modo de intoxicarse sufre con el paso de los [0212-7199 (2008) Conclusiones: este año ha supuesto un importante aumento (34%) del número de casos y la incidencia supera a todas las publicadas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
3
1
3
Order By: Relevance
“…Both sexes were equally represented in our study, which contrasts with the female predominance that is often observed [14] and the male predominance among those treated only in a pre-hospital setting [15]. …”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Both sexes were equally represented in our study, which contrasts with the female predominance that is often observed [14] and the male predominance among those treated only in a pre-hospital setting [15]. …”
Section: Discussioncontrasting
confidence: 71%
“…The incidence of hospitalized acute poisonings in Oslo was similar to that in 2003 [3], but marginally lower than the only large prospective study conducted in Europe, which was the Spanish VEIA 2004 study (2.3 per 1000) [14]. In contrast to Spain and most other countries, a separate emergency outpatient clinic (EMA) in Oslo treats the majority of substance abuse poisonings that would otherwise be present in hospital emergency departments (e.g., ethanol, opioid, and stimulants).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The present male predominance, unchanged from 2003, reflects the higher prevalence of substance abuse among males [2,11]. In contrast to hospital-treated poisonings, which comprise mainly suicide attempts [6,12-14], AOSAs predominated at the EMA.…”
Section: Discussionmentioning
confidence: 99%
“…En nuestra serie, un 47,7% de las intoxicaciones por heroína también dieron positivo a cocaína, resultado que está descrito como un patrón frecuente entre los consumidores de heroína (Barrio, Bravo y de la Fuente, 2000). Por otra parte, ya desde la década de los 90 se habla de la importancia de las asociaciones entre sustancias, principalmente cuando una de ellas es el alcohol (Stein, Bonanno, O´Sullivan y Watchel, 1993), así, en nuestro estudio también se observa la frecuente asociación entre dos sustancias: alcohol y cocaína, alcohol y cannabis, y cocaína y cannabis, resultado que coincide con lo registrado en otros trabajos publicados en nuestro país (Galicia, Nogué, Sanjurjo y Miro, 2008;Caballero et al, 2008;Sanjurjo, Montori, Nogué, Sánchez y Munné, 2006). Al igual que en otras series (Fernández et al, 2003;Medina et al, 2008), en nuestro trabajo también se aprecia como la mayoría de las intoxicaciones exclusivamente medicamentosas están motivadas por un intento de suicidio en el que, en la mayoría de los casos, están presentes las benzodiacepinas (Lambert, Manel, Bellou y El Kouch, 1997).…”
Section: Discussionunclassified